Integration Dilemma within the Eurasian Space in the Context of the Ukrainian Crisis - Antonina A. Durdyeva (Vestnik MGIMO-Universiteta, 2015)
The article analyses the reaction of top officials, politicians and representatives of the expert community of the Eurasian Economic Union member countries on the aggravation of "Ukrainian crisis" in the context of plans and directions for further Eurasian integration. Today, in the scientific community is becoming a popular" dilemma of integration " as a systematic pattern that determines the development of relations between the integration associations. The dilemma of integration is a political phenomenon, a regular and predictable. Ukrainian crisis, which has become a litmus test of conflict of representations of the CIS countries on the extent and depth of their involvement in the processes of regional integration , most clearly outlined the presence of such dilemma within the CIS. In the current situation for Belarus and Kazakhstan as two , along with Russia , the main designers of the Eurasian field, the dilemma of integration takes a fundamentally different meaning and becomes a so-called "Dilemma of integrations", or contradiction between the desire of these countries to secure the most favorable conditions in its relations with Moscow and reluctance to fully bear the burden of the costs and constraints arising in relations with the EU due to the commitments of the EAEC. Based on the material of the official position of the representatives of Republic of Kazakhstan and the Republic of Belarus the author of the article explores the implications of the Ukrainian crisis in relations of Three: Moscow, Astana and Minsk.